Creativity as a framework for innovation in dental education - Samantha J. Byrne; Solange Glasser (Frontiers Media S.A., 2023)
Dental education is rich with examples of innovation as educators have responded to advances in knowledge, technology, the needs of the community, and most recently the challenges of the COVID-19 pandemic. Current challenges requiring innovative pedagogies include developing graduates who are interprofessional collaborative practice-ready, adapting to technological advances, embedding sustainability in the curriculum, and addressing equity and diversity in dental education. Creativity is the production of something that is novel and useful and is intimately linked to innovation which is the implementation of new and improved ways of doing things. To develop innovative pedagogies and address the current challenges facing dental education, educators and dental schools must reflect on the factors necessary for supporting creativity and innovation and seek to remove barriers to or biases against creativity. Here, we discuss the importance of creativity in supporting innovation in dental education, and call for leadership to actively support all elements of creativity for continued innovation to address the challenges we face in educating the future oral health workforce.